The repentance of a bastard: A study of Violette Leduc - Frantz, Anaïs (Sens public)

(untitled) (Département des littératures de langue française, 2009)
Born spuriously from the union between the son of a well-to-do family and a chambermaid, Violette Leduc finds the means of exerting another kind of authority through autobiographical writing.  It’s the incredible authority of a bastard whose poetic strategy takes the form of repentance – the French word “repentir” can both mean “a feeling of guilt” and “the visible modification applied to a painting”. What with its on-the-spot alterations, the repentance of “La Bâtarde” gives the reader a sense of the immense vitality of an existence presenting itself as being at once in-the-wrong, awkward, and adulterated. The interweaving layers of such a text magnify its complexity.